Buying Prosperity: The Bonusing of Factories at the Lakehead, 1885-1914 - Tronrud, Thorold (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1990)
Though Fort William and Port Arthur (now Thunder Bay) used the full gamut of promotional tools to attract industry in the three decades before 1914, they relied most heavily on bonusing. Together they granted more money in bonuses to manufacturers than perhaps any other community in Canada. Such a policy occasioned much debate locally over the usefulness and propriety of using tax dollars to subsidize industry. This article examines both the extent and effects of bonusing at the Lakehead and the debate it raised. It concludes that while bonuses could, in the short run, greatly affect the rate of industrial growth, the long-term survival of manufacturing depended on favourable geography and a supportive economic environment.